Acute brain swelling due to intraoperative supratentorial subdural hematoma during microvascular decompression: a case report - Shi, Jia; Cao, Jiachao; Zhou, Qiang (Frontiers in Surgery, 2025)
BackgroundMicrovascular decompression (MVD) is the primary treatment for cranial neurovascular compression syndromes. The most critical complication is hemorrhage during or after surgery. Although intraoperative supratentorial subdural hematoma (SDH) is uncommon, its management remains complex and lacks standardization.Case presentationWe report a case of acute brain swelling caused by an intraoperative supratentorial subdural hematoma during microvascular decompression (MVD) for trigeminal neuralgia. By effectively managing intracranial pressure and preventing secondary brain injury, the operation was successfully completed, resulting in a favorable postoperative recovery for the patient.ConclusionThis study examines the presentation and management of acute brain swelling caused by intraoperative supratentorial subdural hematoma (SDH). We aim to highlight the importance of being vigilant for this rare complication during microvascular decompression (MVD), as it can result in fatal brain swelling and encephalocele. Preventing and managing this severe complication remains challenging.